Metabolic programming and monitoring tools in pre-weaned dairy calves. (2nd May 2021) - Plate, Peter
Abstract : The current knowledge on the effects of nutritional and environmental factors in the late embryonic and neonatal phase of dairy calves on performance later in life is summarised. The importance of epigenetic factors is increasingly recognised in this context. Prolonged colostrum feeding, discouraged on most farms to prevent the spread of Johne's disease, can have beneficial effects on the calf's immune system and has been shown to give protection against rotavirus. The importance of colostrum hygiene for uptake of antibodies is explained. Intensive milk or milk replacer feeding leads to a more productive animal while reducing the rearing costs. Iron deficiency anaemia is a common condition in whole milk fed dairy calves, and monitoring haemoglobin and supplementing iron where necessary leads to higher growth rates in calves. Other monitoring tools like lung ultrasound scanning, and beta-hydroxy-butyrate testing at weaning are briefly introduced. In conclusion, the benefits of many early intervention measures are likely to be underestimated.